The Effect of Volume Fraction Variations Epoxy-Rice Straw Composite Fibers with NaOH Treatment on Tensile and Bending Strength - Muhammad Raihan Dwi Wibowo; Cok Istri Putri Kusuma Kencanawati; I Putu Lokantara (Natural Sciences Engineering and Technology Journal, 2023)
Rice straw waste is often a problem for farmers because of the lack of utilization until finally, only burning is done. The use of rice straw for composites aims to increase the economy and maximize the potential of rice straw waste to be more useful in the industry. This research uses epoxy sikadur 52-id mixed hardener in the ratio (2:1) as a matrix, and rice straw fiber as reinforcement, with a fiber length of 3 cm. The composition of fiber and resin uses a volume fraction of 10% fiber: 90% resin, 20% fiber: 80% resin, and 30% fiber: 70% resin. Printing using acrylic prints with a hand lay-up technique. The size of the test specimen refers to ASTM D-3039 for the tensile test and ASTM D790-03 for the bending test. The greatest tensile voltage is found in the volume fraction of 30% fiber of 25,431 MPa. The highest strain occurred in the volume fraction of 30% fiber 1.779. The largest modulus of elasticity comes from the volume fraction of 30% fiber of 1,988 GPa. In the bending test, the largest tensile voltage is found in the volume fraction of 30% fiber, which is 93.260 MPa. The highest strain occurred at a 10% fiber volume fraction of 4.721. The largest modulus of elasticity comes from the volume fraction of 30% fiber which is 3.739 GPa. In both types of testing, it was found that the volume fraction of 30% fiber had the highest tensile and bending strength.